The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/polym14010084
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transfer and Optical Properties of Active PET/PP Food-Grade Films Impregnated with Olive Leaf Extract

Abstract: A supercritical solvent impregnation (SSI) technique was employed to incorporate, by batch- and semicontinuous-modes, bioactive olive leaf extract (OLE) into a food-grade multilayer polyethylene terephthalate/polypropylene (PET/PP) film for active food packaging applications. The inclusion of OLE in the polymer surfaces significantly modified the colour properties of the film. A correlation of 87.06% between the CIELAB colour parameters and the amount of the OLE impregnated in the film was obtained which sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…Then, it would not even be surprising that in Chi-coated samples, higher condensation on the tight surface between the supporting polymer layer that is hydrophobic and the chitosan layer that is hydrophilic might lead to the higher mobility of water vapour molecules and, thus, faster permeation, as seen from higher WVTR values (Table 3). In contrast to the given results, others [53] found that PET/PP food-grade films impregnated with olive leaf extract had a lower WVP after the impregnation. Differences from the present study can be explained by the fact that the used substance was hydrophobic, contrarily to chitosan films that are hydrophilic.…”
Section: Resultscontrasting
confidence: 94%
“…Then, it would not even be surprising that in Chi-coated samples, higher condensation on the tight surface between the supporting polymer layer that is hydrophobic and the chitosan layer that is hydrophilic might lead to the higher mobility of water vapour molecules and, thus, faster permeation, as seen from higher WVTR values (Table 3). In contrast to the given results, others [53] found that PET/PP food-grade films impregnated with olive leaf extract had a lower WVP after the impregnation. Differences from the present study can be explained by the fact that the used substance was hydrophobic, contrarily to chitosan films that are hydrophilic.…”
Section: Resultscontrasting
confidence: 94%
“…And finally, the positive values of b* correlated with the yellow tones of the sample, while its negative values indicate the blue tones. Measurements were carried out using a portable spectrophotometer (CM-2600d, Konica Minolta Co., Osaka, Japan) following the method described by Cejudo et al [46]. In addition, in order to establish the total color difference between the functionalized films and their corresponding control samples, the ∆E index, calculated according to Equation (7):…”
Section: Optical Properties Of the Filmsmentioning
confidence: 99%
“…Poly­(ethylene terephthalate) (PET) has remarkably stable physicochemical properties including excellent chemical resistance, great tensile strength, and high stability in a large temperature range. , PET has thus been used as an indispensable industrial material for a large variety of applications, including making packaging covers, containers, electronic devices, etc. Specifically, PET is intensively used to produce textile fibers because of its excellent mechanical strength, wrinkle resistance, and excellent friction resistance. , Nevertheless, the high surface gloss of PET has made the fibers difficult to be applied into a larger context of usage. , A practical solution to modify the optical properties of PET fibers is to load nano-sized fillers with light-extinction property, such as TiO 2 nanoparticles, into the PET matrix. The method of particle loading can either be online addition, in which the masterbatches containing TiO 2 nanoparticles are melted and mixed with PET chips, followed by melt spinning to get the nanocomposite fiber (Figure ).…”
Section: Introductionmentioning
confidence: 99%